158k views
5 votes
Simplify the product using the distributive property.

(3h - 7 ) ( 3h - 6)
A. 9h² + 3h - 42.
B. 9h² - 3h - 42.
C. 9h²- 39h + 42
D. 9h² + 39h + 42

2 Answers

2 votes
to use the ditrib property you have to do the follwing
(3h-7)(3h-6)= (3h * 3h - 3h*6-7 * 3h +48)=9h^2 - 18h-21h+48= 9h^2 -39h +48
is choice C
User HossBender
by
7.7k points
6 votes
same as last time. you would use FOIL
F)3h*3h= 9h²
O)3h*-6= -18h
I) -7*3h= -21h
L) -7*-6=42
finished equation is: 9h²-39h+42
User Harminder Singh
by
7.1k points